2012
DOI: 10.1016/j.neuroimage.2011.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility induced gray–white matter MRI contrast in the human brain

Abstract: MR phase images have shown significantly improved contrast between cortical gray and white matter regions compared to magnitude images obtained with gradient echo sequences. A variety of underlying biophysical mechanisms (including iron, blood, myelin content, macromolecular chemical exchange, and fiber orientation) have been suggested to account for this observation but assessing the individual contribution of these factors is limited in vivo.For a closer investigation of iron and myelin induced susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
112
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 38 publications
9
112
3
Order By: Relevance
“…8 Interestingly, the globus pallidus showed an inverse relationship of age with mean phase, suggesting that in this structure, the overall phase increases over time. This finding is in contrast to previous histologic publications 1 and may be due to the effect of the relatively high myelin content of the structure on MR imaging phase 38 or the presence of diamagnetic substances (eg, calcium) in elderly subjects. 39 However, a recent phase-imaging study also found slightly increased phase in older subjects.…”
Section: Aging Phase Behaviorcontrasting
confidence: 99%
“…8 Interestingly, the globus pallidus showed an inverse relationship of age with mean phase, suggesting that in this structure, the overall phase increases over time. This finding is in contrast to previous histologic publications 1 and may be due to the effect of the relatively high myelin content of the structure on MR imaging phase 38 or the presence of diamagnetic substances (eg, calcium) in elderly subjects. 39 However, a recent phase-imaging study also found slightly increased phase in older subjects.…”
Section: Aging Phase Behaviorcontrasting
confidence: 99%
“…Future longitudinal studies may benefit from including several iron imaging methods to allow potentially more sensitive and more specific measurements (Haacke et al, 2015). Validity of R2* as an index of iron content may be also threatened by regional differences in myelination (Fukunaga et al, 2010;Langkammer et al, 2012;Lodygensky et al, 2012), although myelin-related bias in estimates of age differences in striatal iron is likely negligible (Daugherty and Raz, 2013). In contrast to the striatum, Hc may contain noniron components that affect R2*, e.g., myelin or amyloid (Quintana et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has to be noted that diamagnetic substances do not always show low signal on phase images; when considering the relative susceptibilities of substances to water susceptibility, substances less diamagnetic than water (such as lipids) might cause a quasi-paramagnetic effect and show high signal on PHA images. 31 However, very few studies using SWI have involved the CMJ, 14,25 and to the best of our knowledge, there has been no report of the local histological characteristics of interlobar differences in the CMJ.…”
Section: Discussionmentioning
confidence: 99%
“…10 The presence of deoxyhemoglobin in the venules of the CMJ will affect both MAG and PHA images. [11][12][13] Effects of myelin and other histological components at the CMJ appear mainly on PHA images, 14 and a recent study reported the disappearance of the CMJ signal on PHA images of demyelinated mice brains. 15 Water-macromolecule exchange has been reported as another cause of contrast on PHA images.…”
Section: Introductionmentioning
confidence: 99%